Country of Origin Labeling (COOL) - Chad Carr; Larry Eubanks (EDIS)
Revised! AN207, a 3-page fact sheet by Chad Carr and Larry Eubanks, describes the COOL labeling regulations for agricultural commodities, including the interim final rule released by AMS on July 28, 2008. Includes references. Published by the UF Department of Animal Science, August 2008.